Gender equality and social inclusion in a just energy transition - Buchy, Marlene; Shakya, Shristi (Think20 (T20). Task Force 6 - Accelerating SDGs: Exploring New Pathways to the 2030 Agenda, 2023)
Universal access to affordable clean energy continues to be a challenge across the globe. Women’s and marginalised groups’ access to clean energy services and green technologies remains constrained by intersectional social factors and gender-blind policies. The recurrent failure of policies to consider differentiated gender and social inclusion needs is a significant obstacle to sustainable development. Underlining the concepts of energy poverty and energy justice, this Policy Brief identifies the key institutional and social constraints to addressing issues of gender equality and social inclusion (GESI) in energy policy in the South Asian region. Studying the case of Nepal, the brief makes recommendations on how to facilitate a gender- and socially inclusive energy transition. These include developing evidence-based gender policies and socially inclusive energy policies; fostering a government culture of intersectoral collaboration; and investing in a workforce able to address the technological challenges to achieving energy justice.